Effect of Transformational Leadership Style and Career Development on the Performance of Health Workers with mediated by Commitment Factor - Dewi, Sandra; Sudiono, David; Anindita, Rina (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: The role of leadership is very necessary in influencing employee performance. Objective: The study aimed to examine the effect of transformational leadership style and career development on the performance of health workers mediated by the commitment of health workers at the MRCCC Siloam Hospital, Jakarta. Method: This study uses associative quantitative methods, namely research using path analysis models and hypotheses. The population of this study were all health workers at the MRCCC Siloam Hospital, Jakarta, which found 689 people. The sample selection used a non-probability sampling technique with purposive sampling method, based on the slovin sample formula, there were 88 respondents. Data collection techniques were carried out by distributing questionnaires through google form and collecting journals and supporting book variables. The data analysis technique uses the SEM-PLS equation model. Result: The results showed that simultaneously leadership style and career development have a significant effect on the performance and commitment of health workers at the MRCCC Siloam Hospital, Jakarta. Transformational leadership style and career development partially have a significant effect on commitment and performance of health workers. Transformational leadership style has a significant effect on the performance of health workers mediated by the commitment of health workers. Career development has a significant effect on performance mediated by the commitment of health workers